The effectiveness of students helping students technique In improving learners’ english grammar - Muhammad Rafiq; Sukmawaty Sukmawaty (Journal of Educational Science and Technology (EST), 2018)
This research was carried out at School of Health Science Makassar. The aims of the study were to assess the use of students helping students technique in assessing students’ grammar achievement. The objects of the study were 42 students in second semester of nursing department. The students were divided into two groups, 22 students were in experimental group and 20 students were in control group. The research employed a quasi-experimental with experimental and control group. In the experimental group, students helping students technique was used for grammar activities, while traditional grouping technique was employed in control group. The data were obtained from grammar test with pre- test, and post-test. The result of this research indicated that the uses of Cooperative Learning of Students helping Students technique in students’ grammar achievement were improved more significantly than the traditional grouping technique. The result of independent sample t-test indicated that t-observed value 3.272 was higher than t-table value 2.021.